GENDER AMBIGUITY AND HUMAN DIGNITY IN ISLAM: A Hermeneutic Reassessment of Prophetic Traditions on Mukhannats - Isyfi Hayati; Mukhammad Zamzami; Wael Hegazy; Muktafi Muktafi; Muhammad Lutfi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
In contemporary Indonesia, waria-a culturally specific category of gender nonconformity-continue to experience religious marginalization, often justified through rigid readings of Prophetic traditions on cross-dressing (takhannuts). Beyond juridical debate, this exclusion raises fundamental questions of human dignity and religious belonging. This article re-examines canonical hadîts narrations on the mukhannath using Jorge J. E. Gracia’s functional hermeneutics, drawing on reports in Shahîh al-Bukhârî and Shahîh alongside their classical commentaries. The study advances three arguments: first, gender ambiguity was recognized in early Islam as a lived social reality rather than a moral anomaly; second, the hadîts corpus distinguishes between innate disposition (min ashl al-khilqah) and deliberate imitation (tasyabbuh), directing censure toward intentional misconduct; and third, a functional hermeneutic reading reveals an ethical orientation toward mercy, proportionality, and the preservation of human dignity. These findings support a dignity-centered interpretive framework that affirms waria as legitimate worshippers (mushallî) and full moral subjects within the Muslim community.